2012
DOI: 10.1158/0008-5472.can-11-3907
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 Stimulates Tumor Growth by Increasing Fibronectin Fibril Assembly in the Tumor Microenvironment

Abstract: The tumor microenvironment, including stromal myofibroblasts and associated matrix proteins, regulates cancer cell invasion and proliferation. Here we report that neuropilin-1 (NRP-1) orchestrates communications between myofibroblasts and soluble fibronectin (FN) that promote α5β1 integrin-dependent FN fibril assembly, matrix stiffness, and tumor growth. Tumor growth and FN fibril assembly was reduced by genetic depletion or antibody neutralization of NRP-1 from stromal myofibroblasts in vivo. Mechanistically,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 49 publications
2
131
0
1
Order By: Relevance
“…We hypothesized that adhesion between exosomes and HSC may require ligand/receptor interactions to facilitate chemotactic signaling. FN is a glycoprotein of the extracellular matrix that is secreted by EC during liver fibrosis (27,(35)(36)(37)42). Indeed, exosomes contained FN, as detected by FN immunogold labeling (Fig.…”
Section: Fn-integrin Interactions Contribute To Exosome Adhesion and mentioning
confidence: 87%
See 1 more Smart Citation
“…We hypothesized that adhesion between exosomes and HSC may require ligand/receptor interactions to facilitate chemotactic signaling. FN is a glycoprotein of the extracellular matrix that is secreted by EC during liver fibrosis (27,(35)(36)(37)42). Indeed, exosomes contained FN, as detected by FN immunogold labeling (Fig.…”
Section: Fn-integrin Interactions Contribute To Exosome Adhesion and mentioning
confidence: 87%
“…SK1 is an enzyme that produces the HSC chemotactic factor S1P. Additionally, active SK1 enzyme has been detected in the extracellular environment, although not specifically within an exosome fraction (24,25,27,(35)(36)(37). We therefore focused on SK1-derived S1P as a potential pathway relevant to our model of EC-HSC interaction.…”
Section: Sk1 Is An Ec-derived Exosome Protein-becausementioning
confidence: 99%
“…For this purpose, we overexpressed a NRP-1 mutant that lacked the SEA domain (NRP-1ΔSEA), as this protein is unable to bind synectin (9). For control purposes, we overexpressed WT NRP-1.…”
Section: Synectin Regulates Pdgfr Protein Levelsmentioning
confidence: 99%
“…Synectin (also referred to in the literature as GIPC) contains a PDZ domain that mediates the binding of multiple transmembrane proteins either directly or through coreceptors, such as the glycoprotein neuropilin-1 (NRP-1) (8,9). Previous work showed that synectin, with its NRP-1 binding partner, played a key role in fibronectin fibril assembly in tumor-associated myofibroblasts (9), raising the possibility that a similar phenomenon may take place in broader pathological conditions such as liver fibrosis; this is a phenomenon, however, that awaits experimental confirmation. Moreover, the effects that synectin has on the regulation of PDGFRs and their downstream fibrogenic response have not been examined, leading us to the present study aimed at investigating the role of this protein on PDGFR signaling and cellular functions in HSC.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has implicated NRPs in the regulation of integrin function (reviewed in Goel et al, 2012;Goel and Mercurio, 2013). NRP1 has been shown to promote a5b1 activation and function in both matrix assembly (Yaqoob et al, 2012) and endothelial cell adhesion to fibronectin (Valdembri et al, 2009). Our studies now present evidence that the a5b1 integrin can regulate NRP1 function, thus demonstrating the bidirectionality of integrin-NRP1 crosstalk.…”
Section: Discussionmentioning
confidence: 99%